Dynamic Coloration of Complex Emulsions by Localization of Gold Rings Near the Triphase Junction. Issue 12 (19th February 2021) - Ku, Kang Hee; McDonald, Benjamin R.; Vijayamohanan, Harikrishnan; Zentner, Cassandra A.; Nagelberg, Sara; Kolle, Mathias; Swager, Timothy M.
Abstract: Multiphase microscale emulsions are a material platform that can be tuned and dynamically configured by a variety of chemical and physical phenomena, rendering them inexpensive and broadly programmable optical transducers. Interface engineering underpins many of these sensing schemes but typically focuses on manipulating a single interface, while engineering of the multiphase junctions of complex emulsions remains underexplored. Herein, multiphilic triblock copolymer surfactants are synthesized and assembled at the triphase junction of a dynamically reconfigurable biphasic emulsion. Tailoring the linear structure and composition of the polymer surfactants provides affinity to each phase of the complex emulsion (hydrocarbon, fluorocarbon, and continuous water phase), yielding selective localization of polymers around the triphase junction. Conjugation of these polymers with gold nanoparticles, forming structured rings, affords a dynamic reflected isotropic structural color that tracks with emulsion morphology, demonstrating the uniquely enabling nature of a functionalized triphase interface. This color is the result of interference of light along the internal hydrocarbon/fluorocarbon interface, with the gold nanoparticles scattering and redirecting light into total internal reflection competent paths. Thus, the functionalization of the triphase junction renders complex emulsions colorimetric sensors, a powerful tool toward sensitive and simple sensing platforms. Abstract : Multiphilic triblcok copolymer surfactants are developed to manipulate the biphasic emulsion shape and optical behavior. Site‐specific conjugation of gold nanoparticles enables the creation of gold rings along the triphase junction, which isotropize the structural colors. Dynamic behavior of complex emulsions is imparted to the gold rings, affording the visualization of emulsion shape into the specific color reflection.